Deltagende borgere i Energibyen Frederikshavn - Anders Horsbøl; Lisbeth Eeg (Akademisk Kvarter, 2012)
Anders Horsbøl and Lisbeth Eeg Deltagende borgere i Energibyen Frederikshavn (Participating citizen in the Energy City of Frederikshavn). Denmark has some experience with local participation of citizens in projects in which energy saving "green" or sustainable approaches are developed bottom-up. This article focusses on the participating citizens in such an initiative – the Energy City of Frederikshavn – which among other things can praise itself of an ambition of total use of renewable energy in 2015. Based on an analysis of citizens' meetings and interviews with the participants we examine what motives and values the participants stated they had, and what social identities they realized, and how close everyday life is linked to more far-reaching issues.